A Model For Developing Students' Labor Upbringing Technologies In The Context Of Traditional Karakalpak Folk Pedagogy - Doshniyazov, Jarlikasin (Jurnal Teknologi Pendidikan, 2025)
This article explores the development of students' labor upbringing technologies within the framework of traditional Karakalpak folk pedagogy. The study highlights the importance of connecting historical roots with modern pedagogical approaches to foster creativity, independence, and initiative in students. A model was developed and implemented to promote students' active participation in labor activities, emphasizing the acquisition of professional skills, motivation, and creative problem-solving abilities. The research outlines criteria for assessing students’ labor activity, such as motivation, cognitive skills, practical capabilities, methodological understanding, and personal creativity. By integrating traditional Karakalpak crafts into educational activities, the study underscores the value of preserving cultural heritage while preparing students for modern technological and professional demands. Findings demonstrate the model’s effectiveness in fostering students’ creativity, independence, and adaptability, thus contributing to their holistic development and readiness for future professional challenges.